Genomic analysis of carbapenem-resistant Klebsiella pneumoniae blood isolates from nationwide surveillance in South Korea - On, Younggwon; Kim, Jung Wook; Lee, Juyoung; Yoo, Jung Sik (Frontiers in Microbiology, 2025)
IntroductionCarbapenem-resistant Klebsiella pneumoniae (CRKP) poses a significant threat to public health owing to its multidrug resistance and rapid dissemination.MethodsThis study analyzed CRKP isolates collected from bloodstream infections in nine regions of South Korea using the Kor-GLASS surveillance system between 2017 and 2021.ResultsA total of 3,941 K. pneumoniae isolates were collected. Among them, 119 (3%) isolates were identified as CRKP. Most CRKP (79.7%) belonged to sequence type 307 (ST307), followed by ST11 (6.8%). All CRKP isolates exhibited multidrug resistance, with 78.8% carrying the IncX3 plasmid encoding the KPC-2 gene. Phylogenetic and genomic analyses revealed that ST307 isolates exhibited low single nucleotide polymorphism (SNP) differences. SNP differences among ST307 strains ranged from a minimum of 1 to a maximum of 140, indicating close genetic relatedness. All ST307 strains harbored the KL102 and O1/O2v2 loci, and genomic analysis revealed high prevalence of key resistance genes such as KPC (91.5%) and CTX-M-15 (83.9%), alongside mutations in the QRDR (ParC-80I, GyrA-83I) and ompK genes. Two major clusters were identified, with cluster 1 harboring yersiniabactin lineage 16 (ICEkp12) and cluster 2 showing higher virulence, including the yersiniabactin lineage 17 (ICEkp10) and colibactin-associated genes.DiscussionThese findings underscore the dominance of ST307 among CRKP isolates in Korea, which is driven by clonal expansion and the critical role of mobile genetic elements. Therefore, enhanced genomic surveillance and targeted infection control measures are urgently required to address the spread of CRKP in clinical settings.